2016
DOI: 10.15446/revfacmed.v64n3.53961
|View full text |Cite
|
Sign up to set email alerts
|

Intensive chemotherapy in children with acute lymphoblastic leukemia. Interim analysis in a referral center in Colombia.

Abstract: Background: Acute lymphoblastic leukemia is the most common cancer in children. In developed countries, overall survival rates are around 80%, while in developing countries, survival rate is much lower due to high rates of relapse, and abandonment and complications arising from the disease treatment.Objectives: To assess induction mortality, relapse and treatment abandonment. To describe the most frequent side effects of chemotherapy. To evaluate survival rates of patients and compare the findings found in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 0 publications
0
6
0
6
Order By: Relevance
“…Though its survivor rate has increased due to improved treatment regimens and supportive care, still it has high mortality in resource constraint country like Pakistan. [19][20] In our study 56.6% had one complication and 25% had several complications. Oeffinger et al 21 reported that among ALL survivors, 62.3% had one complication.…”
Section: Discussionmentioning
confidence: 66%
“…Though its survivor rate has increased due to improved treatment regimens and supportive care, still it has high mortality in resource constraint country like Pakistan. [19][20] In our study 56.6% had one complication and 25% had several complications. Oeffinger et al 21 reported that among ALL survivors, 62.3% had one complication.…”
Section: Discussionmentioning
confidence: 66%
“…Today, the mortality rate from complications of ALL in children and its therapy remains high and exceeds the mortality rate from relapse of leukaemia 2,20 . These data are the same as ours: 3 (6.5%) children out of 46 died from complications of the underlying disease, complications of therapy, or a combination of these two pathological conditions.…”
Section: Discussionmentioning
confidence: 99%
“…En la población pediátrica se concluyó que el protocolo IB de intensidad aumentada parece mejorar la sobrevida en pacientes pediátricos con LLA de alto riesgo, pero con una mayor toxicidad, siendo el evento más frecuente la reacción alérgica a la asparaginasa nativa. Considerando que, en nuestro contexto, se reporta gran porcentaje de pacientes que presentan reacciones alérgicas a la asparaginasa nativa, produciendo una interrupción de la quimioterapia; que los pacientes peruanos tienen un estado nutricional diferente a los que participaron en los estudios presentados [35] , conllevando a un mayor riesgo y frecuencia de toxicidad a la terapia; y existen estudios observacionales en poblaciones latinoamericanas con características similares a la peruana que reportan menos supervivencia en pacientes que utilizaron IB de intensidad aumentada [36] ; el GEG concluyó en brindar una recomendación a favor del uso del protocolo IB estándar. Debido a que la certeza de la evidencia para todos los desenlaces muy baja, se decidió asignarle una fuerza condicional a esta recomendación.…”
Section: Bpc-42unclassified
“…BPC-6.1: El protocolo de investigación ALL IC-BFM 2009 tiene entre sus objetivos determinar la mejor dosis de metotrexato (2000 mg/m 2 /día vs 5000 mg/m 2 /día como dosis total administradas por día de metotrexato) para pacientes con riesgo intermedio de linaje B [17] . Una cohorte de pacientes colombianos con LLA de linaje B y T de riesgo estándar e intermedio (N=119) que recibían el protocolo ALL IC-BFM 2009, usó dosis de metotrexato de 2000 mg/m 2 /día y 5000 mg/m 2 /día, sin realizar comparaciones, encontrándose una supervivencia global y libre de eventos de 79,9% y 73,3%, respectivamente [36] .…”
Section: Bpc-42unclassified